Analysis of Soil Quality Around Biopore Infiltration Pits in Ciputri Village - Dewi, Ratna Sari; Ahmad Mughofar (WISE Pendidikan Indonesia, 2024)
Soil quality is the capacity of land to provide functions needed by humans and ecosystems over a long period of time. Soil quality indicators are physical, chemical and biological properties of the soil that describe the condition of the soil. Biopore infiltration holes are a technology used to increase water recharge, utilizing the role of soil fauna and plant root activities. This study aims to determine the quality of soil on residential land as a result of the application of biopore holes. The research was conducted on residential land in Ciherang Hamlet, Ciputri Village, Cianjur Regency from April to October 2023, using experimental methods and laboratory analysis. Data analysis using the LandPKS application and Shanon Wiener formula and Lowery scoring method. The results showed that the dominant soil color was dark. pH and C-Organic soils are interconnected. The soil pH obtained ranges from 5.6 - 7.6 with an average of 6.87 which indicates an acidic pH and safe for macrofaunal life. C-Organic soil has increased with moderate category after average, C-Organic has increased because pH has increased. Macroorganisms have increased the number of families, from 6 families to 11 families with a medium diversity index and a high evenness index. Biopore holes filled with organic waste from food waste affect soil quality.